2019
DOI: 10.3390/ijms20163860
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Transcription of BrGA20ox3 by a BrTCP21 Transcription Factor Is Associated with Gibberellin-Delayed Leaf Senescence in Chinese Flowering Cabbage during Storage

Abstract: Several lines of evidence have implicated the involvement of the phytohormone gibberellin (GA) in modulating leaf senescence in plants. However, upstream transcription factors (TFs) that regulate GA biosynthesis in association with GA-mediated leaf senescence remain elusive. In the current study, we report the possible involvement of a TEOSINTE BRANCHED1/CYCLOIDEA/PCF (TCP) TF BrTCP21 in GA-delayed leaf senescence in Chinese flowering cabbage. Exogenous GA3 treatment maintained a higher value of maximum PSII q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Furthermore, melatonin application significantly repressed the transcript level of the DELLA protein-encoding gene GAI (used for GA deactivation or as a GA suppressor) as well as GA catabolic regulating gene ( GA2ox1 and GA2ox2 ) expression ( Figure 6D ). Our findings are also supported by previous works, which noted that the application of GA delays natural or stress-induced leaf senescence ( Fan J. et al, 2018 ; Xiao et al, 2019 ). The supplementation with melatonin increases active GAs under salinity stress in cucumber seedlings by amplifying GA biosynthetic genes ( Zhang N. et al, 2014 ) and delays plant senescence by preventing ROS production and optimizing antioxidant enzyme activities ( Wang et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, melatonin application significantly repressed the transcript level of the DELLA protein-encoding gene GAI (used for GA deactivation or as a GA suppressor) as well as GA catabolic regulating gene ( GA2ox1 and GA2ox2 ) expression ( Figure 6D ). Our findings are also supported by previous works, which noted that the application of GA delays natural or stress-induced leaf senescence ( Fan J. et al, 2018 ; Xiao et al, 2019 ). The supplementation with melatonin increases active GAs under salinity stress in cucumber seedlings by amplifying GA biosynthetic genes ( Zhang N. et al, 2014 ) and delays plant senescence by preventing ROS production and optimizing antioxidant enzyme activities ( Wang et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…Bioactive GA is an essential element that plays an active role in delaying leaf senescence in plants subjected to stressful environments ( Fan J. et al, 2018 ; Xiao et al, 2019 ). In the present investigation, the content of endogenous GA accumulation along with GA biosynthetic encoding enzyme gene ( GA20ox1 and GA20ox2 ) expression was significantly elevated in melatonin-treated plants under heat stress conditions, and the opposite trend was notified in only heat-stressed seedlings ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of plant PCD is strictly mediated by hormonal signals, such as ethylene, ABA, SA and JA [ 32 , 33 ]. In addition, several recent studies have indicated that effects of plant hormones are symbiotic or opposite throughout leaf senescence [ 34 , 35 , 36 ]. The expression trends of SlBAG2 and SlBAG5b after treatment with these four hormones were respectively similar.…”
Section: Discussionmentioning
confidence: 99%
“…The GA 2-oxidase 2 (GA2OX2) gene, which causes GA inactivation, is up-regulated 18-fold during leaf senescence (van der Graaff et al, 2006 ), suggesting that the decrease in active GA may be a cause of leaf senescence. TEOSINTE BRANCHED1/CYCLOIDEA/PCF (TCP) TF BrTCP21 directly binds the promoter of GA biosynthetic gene BrGA20ox3 , activates its transcription, and delays leaf senescence (Xiao et al, 2019 ). The transcript of BrTCP21 decreases along with leaf senescence, while GA 3 treatment keeps BrTCP21 expression in a higher level, which suggests that the positive feedback loop of GA-BrTCP21-GA plays an important role in leaf senescence.…”
Section: Plant Hormones That Delay Leaf Senescencementioning
confidence: 99%